MODELS FOR DETECTING DEFECTIVE FABRICS IN KNITTED PRODUCTS (Academicia Globe: Inderscience Research, 2023)
This article addresses the development and application of models for the detection of defective fabrics in knitted products. With the increasing demand for quality assurance in the textile industry, the implementation of efficient and accurate detection systems is imperative. This study explores existing models, their methodologies, and presents a novel approach to enhance the detection of defects in knitted fabrics. The research aims to contribute to the improvement of product quality, production efficiency, and overall customer satisfaction in the textile manufacturing sector.